The Pseudo-Protic Ionic Liquids TOAH+Cl− and TODAH+Cl− as Carriers for Facilitated Transport of In(III) from HCl Solutions - Francisco José Alguacil; Félix Antonio López (Membranes, 2022)
A study of indium(III) transport across an immobilized liquid membrane using the pseudo-protic ionic liquids TOAH+Cl− and TODAH+Cl− as carriers has been carried out using batch experiments. Metal transport is investigated as a function of different variables: hydrodynamic conditions in the feed (375–1500 min−1) and receiving (500–750 min−1) phases, HCl (0.5–7 M) and indium (0.01–0.2 g/L) concentrations in the feed phase and carrier (1.25–40% v/v) concentration in the membrane phase. Indium is conveniently recovered in the receiving phase, using a 0.1 M HCl solution. Models are reported describing the transport mechanism, which consists of a diffusion process through the feed aqueous diffusion layer, fast interfacial chemical reaction, and diffusion of the respective indium-pseudo-protic ionic liquid through the membrane. The equations describing the rate of transport are derived by correlating the membrane permeability coefficient to diffusional and equilibrium parameters as well as the chemical composition of the respective indium-pseudo-protic ionic liquid system, i.e., the carrier concentration in the membrane phase. The models allow us to estimate diffusional parameters associated with each of the systems; in addition, the minimum thickness of the feed boundary layer is calculated as 3.3 × 10−3 cm and 4.3 × 10−3 cm for the In-TOAH+Cl− and In-TODAH+Cl− systems, respectively.